Visual Motion Coherence Responses in Human Visual Cortex - Rina, Andriani; Papanikolaou, Amalia; Zong, Xiaopeng; Papageorgiou, Dorina T.; Keliris, Georgios A.; Smirnakis, Stelios M. (Frontiers in Neuroscience, 2022)
Random dot kinematograms (RDKs) have recently been used to train subjects with cortical scotomas to perform direction of motion discrimination, partially restoring visual motion perception. To study recovery of visual perception, it is important to first understand how visual areas in normal subjects respond to RDK stimuli. Studies in normal subjects have shown that Blood Oxygen Level Dependent (BOLD) responses in human area hV5/MT+ increase monotonically with coherence, in general agreement with electrophysiology studies in primates. However, RDK responses in prior studies were obtained while the subject was performing fixation, not a motion discrimination condition. Furthermore, BOLD responses were gauged against a baseline condition of uniform illumination or static dots, potentially decreasing the specificity of responses for the spatial integration of local motion signals (motion coherence). Here we revisit this question starting from a baseline RDK condition of no coherence, thereby isolating the component of BOLD response due specifically to the spatial integration of local motion signals. In agreement with prior studies, we found that responses in area hV5/MT+ were monotonically increasing when subjects fixated without performing a motion discrimination task. In contrast, when subjects were performing an RDK direction of motion discrimination task, responses in area hV5/MT+ remained flat, changing minimally, if at all, as a function of motion coherence. These observations shed further light on how normal visual cortex responses behave as a function of motion coherence, preparing the ground for using these methods to study visual system recovery after injury.